2020
DOI: 10.1556/1886.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immune status on the airborne colonization of piglets with methicillin-resistant staphylococcus aureus (MRSA) clonal complex (CC) 398

Abstract: Colonized vertebrates including humans and pigs are to date the main reservoirs of livestock-associated Methicillin-resistant Staphylococcus aureus (LA-MRSA). Currently, the mechanisms underlying colonization of pigs are not fully understood. We investigated the influence of piglet pre-immune status on airborne MRSA colonization. Three groups of MRSA-negative piglets were primed and exposed to airborne LA-MRSA (104 colony forming … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It has been proposed that the piglets' immature immune system might affect their susceptibility to LA-MRSA . However, a recent study could not find a connection between piglets' immune status and LA-MRSA colonisation (Rosen et al 2020). The LA-MRSA colonisation dynamics in sows and gilts during breeding and gestation are also poorly understood.…”
Section: La-mrsa In Pigsmentioning
confidence: 94%
“…It has been proposed that the piglets' immature immune system might affect their susceptibility to LA-MRSA . However, a recent study could not find a connection between piglets' immune status and LA-MRSA colonisation (Rosen et al 2020). The LA-MRSA colonisation dynamics in sows and gilts during breeding and gestation are also poorly understood.…”
Section: La-mrsa In Pigsmentioning
confidence: 94%
“…Livestock-associated-methicillin-resistant S. aureus can also be transmitted from sows to piglets [100,[104][105][106]]. An experimental study demonstrated the transmission of LA-MRSA from sows to all newborn piglets [107].…”
Section: Pig-pig Transmissionmentioning
confidence: 99%
“…However, LA-MRSA was also seen in piglets from LA-MRSA-negative sows, indicating the involvement of other factors. In this context, Rosen et al [106] reported differences in LA-MRSA colonization between different farrow-to-finish pig farms, that is, farms with high LA-MRSA colonization to those with low LA-MRSA colonization. In this study, each pig farm can be considered a closed system where different factors, such as environmental pollution, may affect the LA-MRSA colonization in pigs.…”
Section: Pig-pig Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, new antimicrobial molecules are the focus of current research, but the use of immunostimulants to increase animal resilience at critical phases of animal production is a strategy that is also gaining interest [3]. For example, during the transport, housing, or weaning processes, livestock regularly suffer immunosuppression, metabolic dysregulation, and, as a result, the development of concomitant diseases [4]. In this scenario, immunostimulants hold the potential to boost the immune response to act faster and more efficiently when mitigating opportunistic pathogen infections.…”
Section: Introductionmentioning
confidence: 99%